(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Ibn Khaldun prioritizes the key sociological category of social justice. He advocates for states that are viable only when they adhere to justice and laws. His main goal was to seek ways to serve humanity by addressing social and political problems within the framework of justice. Ibn Khaldun’s methods and approaches to studying the state and society laid the theoretical foundations of sociology. He was the first to analyze state and society from this perspective, establishing Ibn Khaldun as the earliest founder of sociology.